Analisis Kesalahan Siswa Dalam Mengerjakan Soal Cerita Matematika FPB dan KPK di MI Thoriqul Huda - Hidayatus Sa'adah; Durrotun Nihayah; Barudin (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
Mathematics is a universal science that underlies the development of modern technology, has an important role in various scientific disciplines and advances human thinking. Current developments in the field of information and communication technology are based on mathematical developments in the field of number theory, algebra, analysis, probability theory and discrete mathematics. To master and create technology in the future requires mastery of mathematics from an early age. The promblems that we want to find answers to through this research are: a). What are the forms of errors made when working on FPB and KPK?, b). what forms of errors do people most often make when working on FPB and KPK story question?. This type of research uses a qualitative approach with descriptive methods. The data collection techniques used were tests, interviews and documentation. The results showed that more students made conceptual errors. Conceptual errors, namely students in this study made a mistake in determining and using the FPB formula from two numbers as well as KPK. Procedural errors, namely students in this study did not write down known questions and also asked questions, did not make a factor tree or sequential division, did not write down each factor. each number, was wrong in solving the final stage of the question, and there was no conclusion to the answer. Engineering error, namely the students in this study made a mistake in calculating the answer to the question